One-Pot Synthesis of Metal–Carbon Nanotubes Network Hybrids as Highly Efficient Catalysts for Oxygen Evolution Reaction of Water Splitting - Cheng, Yi; Liu, C.; Cheng, H.; Jiang, San Ping (American Chemical Society, 2014)
Oxygen evaluation reaction (OER) is the most important reaction in hydrogen production from watersplitting. Here we developed metal-carbon nanotubes (MCNTs) hybrids with high metal oxide catalyst loading synthesized by arc-discharge and chemical vapor deposition (CVD) methods as electrocatalysts for OER in alkaline solutions. The M-CNTs hybrids produced by arc-discharge(M-CNTs-Arc) and CVD (M-CNTs-CVD) exhibit a core- shell-like structure, in which metal nanoparticles (NPs) encapsulated by graphite shells are connected by carbon nanotubes (CNTs), forming M-CNTs network hybrids. M-CNTs-Arc has NiCo0.16Fe0.34 metal core and shows very high activity and superior stability for OER, achieving 100 A g-1 at an overpotential (?) of 0.29 V and 500 A g-1 at ? = 0.37 V in 1 M KOH solution. This is probably the highest activity reported for OER in alkaline solutions. The reaction follows the first-order kinetics with respect to OH- concentration and Tafel slope of 34 mV dec-1. The results demonstrate a highly efficient, scalable, and lowcost one-step synthesis method for developing highly active and stable catalysts for electrochemical water splitting in alkaline solutions.